2000
DOI: 10.1111/1467-9280.00219
|View full text |Cite
|
Sign up to set email alerts
|

Distress Vocalizations in Infant Rats: What's All the Fuss About?

Abstract: Ultrasonic vocalizations emitted by infant rodents are typically characterized as cries of distress. There are two contexts that are known to reliably elicit ultrasound production: extreme cold exposure and administration of clonidine, an alpha 2 adrenoceptor agonist. Noting that these two contexts both entail pronounced decreases in cardiac rate, we have hypothesized that the vocalizations are acoustic by-products of a physiological maneuver, the abdominal compression reaction (ACR), that increases venous ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Temperature also was not a factor. While chilled pups are licked and groomed more frequently than their control pups (Stern & Johnson, 1990), and chilled pups may vocalize at a higher rate than warm pups depending on their prior isolation history (Blumberg, Sokoloff, Kirby, & Kent, 2000;Hofer et al, 1993), our observed differences in vocalization and maternal behavior were not due to any difference in pups' core temperatures since there were no differences in this measure. Finally, body weight was not a factor in differential call rates because while the Acute Isolates emitted as few calls as the Chronic Isolates compared to Home Nest pups, their body weight was the same as the Home Nest pups and significantly greater than that of the Chronic Isolates.…”
Section: Discussionmentioning
confidence: 62%
“…Temperature also was not a factor. While chilled pups are licked and groomed more frequently than their control pups (Stern & Johnson, 1990), and chilled pups may vocalize at a higher rate than warm pups depending on their prior isolation history (Blumberg, Sokoloff, Kirby, & Kent, 2000;Hofer et al, 1993), our observed differences in vocalization and maternal behavior were not due to any difference in pups' core temperatures since there were no differences in this measure. Finally, body weight was not a factor in differential call rates because while the Acute Isolates emitted as few calls as the Chronic Isolates compared to Home Nest pups, their body weight was the same as the Home Nest pups and significantly greater than that of the Chronic Isolates.…”
Section: Discussionmentioning
confidence: 62%
“…The second version of the epiphenomenon hypothesis suggested that all USV results from a cardiovascular maneuver called the abdominal compression reaction whose function is to increase venous return [9,10,60]. This hypothesis was also disproved [94].…”
Section: Isolation-induced Usv Is Not a By-product Of Thermal Or Cardmentioning
confidence: 99%
“…The first form of the hypothesis argued that all USV results from attempts to increase thermogenesis [6][7][8]. We tested and disproved that hypothesis in several ways: The second version of the epiphenomenon hypothesis suggested that all USV results from a cardiovascular maneuver called the abdominal compression reaction whose function is to increase venous return [9,10,60]. This hypothesis was also disproved [94].…”
mentioning
confidence: 94%
“…Indeed, some data in the present study would be consistent with an earlier developmental change in the relationship between two acoustic parameters (mean peak sound frequency and mean call duration) following prenatal malnutrition (discussed later). The USV characteristics may, at least in part, have been influenced by the proportion of sounds emitted as a by-product of the abdominal compression reaction, a maneuver that assists the flow of blood back to the heart when the pup is cooled (Blumberg et al, 1999;Blumberg et al, 2000). If present, however, this would have had the greatest effect at the youngest age (P7), where significant group differences in body temperature were documented.…”
Section: Usv Call Characteristicsmentioning
confidence: 99%
“…There has been recent debate about the functional significance of such vocalizations, and it has been proposed that some may be simple by-products of the abdominal compression reaction, a maneuver that increases blood flow to the heart in response to a thermal challenge (Blumberg & Sokoloff, 2001;Blumberg, Sokoloff, & Kent, 1999;Blumberg, Sokoloff, Kirby, & Kent, 2000;Kraebel, Brasser, Campbell, Spear, & Spear, 2002). Ethologically, however, there is much evidence to suggest that these calls elicit maternal search and retrieval behavior (Allin & Banks, 1972;Noirot, 1972) and that, together with olfactory cues, they serve as robust directional cues for the localization of the pups (Allin & Banks, 1972;Brunelli, Shair, & Hofer, 1994;Smotherman, Bell, Hershberger, & Coover, 1978).…”
mentioning
confidence: 99%